Experimental Study on the Production of Karanja Oil Methyl Ester and Its Effect on Diesel Engine - Shrivastava, N; Varma, S.N; Pandey, M (International Journal of Renewable Energy Development, 2012)
Fast depletion of fossil fuel resources forces the extensive research on the alternative fuels. Vegetable oils edible or non edible can be a better substitute for the petroleum diesel. Karanja, a non edible oil can be a potential source to replace the diesel fuel. To investigate the feasibility of Karanja oil as an alternative diesel fuel, its biodiesel was prepared through the transesterification process. The Biodiesel was then subjected to performance and emission tests in order to assess its actual performance, when used as a diesel engine fuel. The data generated for the 20, 50 and 100 percent blended biodiesel were compared with base line data generated for neat diesel fuel. Result showed that the Biodiesel and its blend showed lower thermal efficiency. Emission of Carbon monoxide, unburned Hydrocarbon and smoke was found to be reduced where as oxides of nitrogen was higher with biodiesel and its blends.Â Keywords: alternate Diesel fuel; Biodiesel; Karanja oil methyl ester; performance and emission